Assessing the comparative advantage of Malaysian ruminant production: a Policy Analysis Matrix approach - Abd Latif, Ismail; Mohamed, Zainal Abidin; Adha, Zulheri; Shamsudin, Mad Nasir (Universiti Putra Malaysia Press, 2013)
The comparative advantage of ruminant sector is measured in selected state Peninsular Malaysia using a modified Policy Analysis Matrix (PAM) to determine whether ruminant production has comparative advantage if produced under commercial, medium, or small farm size. This study showed that Peninsular Malaysia has a strong comparative advantage in commercial production of ruminant products. The result indicates that producing the one unit value added of ruminant products in commercial farm size can be achieved by using less than one unit of the domestic resource factors. It means that ruminant products in Peninsular Malaysia are more profitable to produce in commercial sized farms than to import them.